Paraspinal Muscle DTI Metrics Predict Muscle Strength. Issue 3 (5th February 2019) - Klupp, Elisabeth; Cervantes, Barbara; Schlaeger, Sarah; Inhuber, Stephanie; Kreuzpointer, Florian; Schwirtz, Ansgar; Rohrmeier, Alexander; Dieckmeyer, Michael; Hedderich, Dennis M.; Diefenbach, Maximilian N.; Freitag, Friedemann; Rummeny, Ernst J.; et al.
Abstract : Background: The paraspinal muscles play an important role in the onset and progression of lower back pain. It would be of clinical interest to identify imaging biomarkers of the paraspinal musculature that are related to muscle function and strength. Diffusion tensor imaging (DTI) enables the microstructural examination of muscle tissue and its pathological changes. Purpose: To investigate associations of DTI parameters of the lumbar paraspinal muscles with isometric strength measurements in healthy volunteers. Study Type: Prospective. Subjects: Twenty‐one healthy subjects (12 male, 9 female; age = 30.1 ± 5.6 years; body mass index [BMI] = 27.5 ± 2.6 kg/m 2 ) were recruited. Field Strength/Sequence: 3 T/single‐shot echo planar imaging (ss‐EPI) DTI in 24 directions; six‐echo 3D spoiled gradient echo sequence for chemical shift encoding‐based water–fat separation. Assessment: Paraspinal muscles at the lumbar spine were examined. Erector spinae muscles were segmented bilaterally; cross‐sectional area (CSA), proton density fat fraction (PDFF), and DTI parameters were calculated. Muscle flexion and extension maximum isometric torque values [Nm] at the back were measured with an isokinetic dynamometer and the ratio of extension to flexion strength (E/F) calculated. Statistical Tests: Pearson correlation coefficients; multivariate regression models. Results: Significant positive correlations were found between the ratio of extension to flexion (E/F) strength and mean diffusivity (MD) ( P  = 0.019), RD ( P  = 0.02) and the eigenvalues (λ1: P  = 0.026, λ2: P  = 0.033, λ3: P  = 0.014). In multivariate regression models λ3 of the erector spinae muscle λ3 and gender remained statistically significant predictors of E/F (R 2 adj  = 0.42, P  = 0.003). Data Conclusion: DTI allowed the identification of muscle microstructure differences related to back muscle function that were not reflected by CSA and PDFF. DTI may potentially track subtle changes of back muscle tissue composition. Level of Evidence : 3 Technical Efficacy : Stage 2 J. Magn. Reson. Imaging 2019;50:816–823.